2010
DOI: 10.1016/j.bbrc.2010.11.065
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and localization of 12/15 lipoxygenases in adipose tissue in human obese subjects

Abstract: Adipose tissue inflammation in obesity is a major factor leading to cardiovascular disease and type 2 diabetes.12/15 lipoxygenases (ALOX) play an important role in the generation of inflammatory mediators, insulin resistance and downstream immune activation in animal models of obesity. However, the expression and roles of 12/15ALOX isoforms, and their cellular sources in human subcutaneous (sc) and omental (om) fat in obesity is unknown. The objective of this study was to examine the gene expression and locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 32 publications
1
39
1
Order By: Relevance
“…Mice with a targeted deletion of 12-/15-LO in adipose tissue are protected from IR and pancreatic islet inflammation, suggesting a key role of AT 12-/15-LO for the onset of IR in obesity (12). We previously reported that ALOX 12, ALOX 15A and ALOX 15B have a depot-and cell-specific expression in human AT that differs from that of animal models of obesity (6), which emphasizes the importance of findings validation in humans (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice with a targeted deletion of 12-/15-LO in adipose tissue are protected from IR and pancreatic islet inflammation, suggesting a key role of AT 12-/15-LO for the onset of IR in obesity (12). We previously reported that ALOX 12, ALOX 15A and ALOX 15B have a depot-and cell-specific expression in human AT that differs from that of animal models of obesity (6), which emphasizes the importance of findings validation in humans (1).…”
Section: Discussionmentioning
confidence: 99%
“…These procedures were described previously (6). Results were normalized to 18S RNA and data were expressed as 1/⌬ cycle threshold.…”
Section: Quantitative Real-time Pcr and Gene Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…In-vitro studies have shown that addition of 12-lipoxygenase and 15-lipoxygenase products to adipocytes induces inflammatory adipokine secretion and impairs insulin action [25]. Finally, Dobrian et al [42], working with subcutaneous and omental tissues from morbidly obese patients, have elegantly demonstrated that 12/15-lipoxygenase is predominantly expressed in visceral fat in which it correlates with increased mRNA levels of IL-6, IL-12, interferon-g, and CXCL10.…”
Section: Lipoxygenases Are Emerging Targets In Metabolic Diseasementioning
confidence: 99%
“…Obesity resulting from expansion of adipose tissue is associated with low-grade inflammation, and lipoxygenase enzymes have been linked to inflammatory changes leading to the development of obesity (Ye 2009;Cole et al 2012;Dobrian et al 2010). Adipocytes express ; studies indicate overexpression of 15-LOX gene in adipocytes isolated from obese rats when compared with lean rats (Sears et al 2009;Chanez et al 2002).…”
Section: Introductionmentioning
confidence: 99%